Strategising corporate identity for the perception of corporate image in the selected government-linked companies (GLCs) in Malaysia - Bidin, Rosmiza; Muhaimi, Aida; Bolong, Jusang (Elsevier, 2014)
A survey has been conducted to audit the corporate image of selected GLCs in Malaysia using corporate identity elements, where data were collected from a sample of middle managers. Correlation analysis was used to analyze the data. Results indicated that all studied elements of corporate identity components (corporate behavior, corporate communication, corporate design, corporate culture, corporate strategy, and corporate personality) have significant contribution towards corporate image. Thus, managers have to carefully strategize these elements in their internal branding initiatives to come out with excellent corporate image.